1998
DOI: 10.1111/j.1469-7998.1998.tb00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology and anatomy of the ‘living fossil’Congeria kusceri (Bivalvia: Dreissenidae) from subterranean rivers and caves in the Dinaric karst of the former Yugoslavia

Abstract: The cave-dwelling Congeria kusceri is described and aspects of its unique ancestry and biology elucidated in the context of its, for a bivalve, similarly unique habitat. The species lives in subterranean waters of the Dinaric karst of the former Yugoslavia. C. kusceri is acutely heteromyarian in form commensurate upon its lifestyle of byssal attachment to the walls of either permanently or periodically inundated karst caves. Shells are sometimes covered by travertine, precipitated calcium carbonate, and the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The relationships of the two widespread extant genera are examined in this study, including the freshwater Dreissena and the estuarine and marine Mytilopsis (Rosenberg and Ludyanskiy, 1994). The genus Congeria was believed to be extinct since the Miocene (Nuttall, 1990) but C. kusceri recently was described living in underground caves in the former Yugoslavia (Morton et al, 1998). Stepien and Skidmore have obtained specimens from Morton and are sequencing them to compare with the results of the present study.…”
Section: Evolutionary Relationships Morphology and Historic Distribmentioning
confidence: 92%
See 2 more Smart Citations
“…The relationships of the two widespread extant genera are examined in this study, including the freshwater Dreissena and the estuarine and marine Mytilopsis (Rosenberg and Ludyanskiy, 1994). The genus Congeria was believed to be extinct since the Miocene (Nuttall, 1990) but C. kusceri recently was described living in underground caves in the former Yugoslavia (Morton et al, 1998). Stepien and Skidmore have obtained specimens from Morton and are sequencing them to compare with the results of the present study.…”
Section: Evolutionary Relationships Morphology and Historic Distribmentioning
confidence: 92%
“…The origin of Corbicula in Asia has not been determinable from allozyme (Smith et al, 1979;McLeod and Sailstad, 1980;Hillis and Patton, 1982) or morphological (Morton, 1996) data. Sequence data hold promise for elucidating the relationships of the heteromyarian dreissenoid genus Congeria, which was believed extinct since the Miocene Epoch (Nuttall, 1990), with C. kusceri recently described as living in underground caves in Slovakia (Morton et al, 1998). Congeria and Mytilopsis are hypothesized to be sister taxa (Nuttall, 1990;Morton et al, 1998), which can be tested with DNA sequence data.…”
Section: Future Directionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously reported temperatures are in the higher range; Morton et al (1998) and Puljas et al (2014) reported temperature of 13.5°C, whereas Jalžić (1998) by a water level rise meaning that an influx of cold water from the surface causes them. For instance, the lowest temperature in Žira and Jama u Predolcu caves was recorded at the same time, in February 2012, and was caused by the water level rise in the whole Trebišnjica river basin.…”
Section: Discussionmentioning
confidence: 99%
“…Congeria mulaomerovici is known from only 3 localities in the Sana River basin in Bosnia and Herzegovina. The most research has been done on C. kusceri (e.g., biology and anatomy, Morton et al, 1998;phylogeny, Stepien et al, 2001; life history, Morton & Puljas, 2013; growth and longevity, Puljas et al, 2014), as some of the caves it inhabits are easily accessible and available for research throughout the year.…”
Section: Introductionmentioning
confidence: 99%